First-Hand Learning Participation: An Empirical Analysis of the Learning Outcomes of Long Term Stay Malaysian Students in Japan - Muhammad Nor, Rahimah; Hassan, Asmadi; Paidi, Rohayati (WILAYAH: The International Journal of East Asian Studies, 2017)
Studying in a foreign country is one of the ways to enhance students’ competencies in facing challenges of global competitiveness and in being marketable for future career choices. This research investigates the impact of cross-cultural adaptation among Malaysian students (N=245) who enrolled in various universities in Japan. Quantitative method was used to examine changes in the following five factors: personal changes, cross-cultural awareness, cross-cultural interaction, global mindedness and intellectual development. The findings demonstrate that studying abroad brings positive outcomes in students’ personal development. Hence, student mobility is an invaluable experience and administrators should support and encourage young people to explore “real life” globally.